MANAJEMEN KEPALA MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI MADRASAH ALIYAH ALCHAIRAAT FALABISAHAYA - Maani Pora (CV. ADIBA AISHA AMIRA, 2023)
The management of madrasa heads plays an important role in improving the quality of education in madrasas. This study aims to determine the planning, organizing, implementing, coordinating, supervising, and evaluating the leadership of the madrasa head in improving the quality of education at Madrasa Aliyah Alchairaat Falabisahaya. Objective: This study aims to find out how the management of madrasa heads can improve the quality of education at Madrasa Aliyah Alchairaat Falabisahaya. Method: This study uses a qualitative approach with data collection techniques through in-depth interviews and observation. Respondents in this study were madrasa heads, teachers, and students at Madrasa Aliyah Alchairaat Falabisahaya. Discussion result: The results of the study show that the management of madrasa heads plays an important role in improving the quality of education in madrasas. The madrasa head has an important role in planning, organizing, implementing, coordinating, supervising, and evaluating leadership. In addition, the madrasa head also acts as a supervisor in an effort to help develop the professionalism of teachers and other education personnel. Therefore, the management of madrasa heads needs to be improved so that the quality of education in madrasas can continue to improve.